Toxicity of building materials: a key issue in sustainable construction - Pacheco-Torgal, F. (2011)
To avoid the use of toxic building materials is one of the principles of sustainable construction. However and contrary to general beliefs, current residential buildings frequently contain many toxic building materials, some of which even comply with legal regulations. Part of the problem is because architects and civil engineers have no form of knowing the toxicity of building materials. The other part is economically related. Some regulations about toxicity limits are influenced by economic reasons. For instance, although scientific evidence about the toxicity of lead plumbing has existed for quite some time, legal regulations avoid imposing very tight thresholds because of the cost of lead pipe substitution (in Europe that could cost almost 200,000 million euros). It is then no surprise to see that the related Directive (98/83/CE) established a 15-year delay period before the 10 mg/l lead content threshold is enforced. This paper discusses some cases of toxic building materials by reviewing previously published work, it also covers the emission of volatile organic compounds from paints and varnishes, the toxicity of impregnating agents, materials that release toxic fumes during a fire, asbestos-based materials, radioactive materials and lead plumbing.